Reframing financial abuse of parishioners: an analysis of a Church of England disciplinary tribunal hearing regarding Rev. Karl Wray. Issue 2 (10th February 2020) - Redmond, Mark
Abstract : Purpose: Traditional understandings of financial abuse are limited to particular situations and people who have close access to vulnerable adults. This paper aims to add to a debate that intends to push the boundaries of the understanding of financial abuse further. In particular, it seeks to add to the understanding of what financial abuse might look like and who the perpetrators of such abuse can be. In so doing, it seeks to offer greater protection to the vulnerable. Design/methodology/approach: Focusing on exploring the minutes of Church of England disciplinary tribunals, held to provide accountability for clergy, this paper considers how the church seeks to represent and construct the victims of financial abuse. Findings: The paper identifies that the victims of financial abuse are whitewashed out of the tribunal minutes and discovers that the disciplinary tribunal is solely concerned with the financial loss afforded by the church. This discovery offers a new context in which it is possible to explore the competing interest in, what has been regarded as, the "legitimate assets" of older parishioners. It provides an example of how organisations and individuals compete for them. Originality/value: This paper adds to the debate about the everyday nature of financial abuse and when and where it might take place. It provides an opportunity to reconsider potential offenders and the means by which abuse might be reduced. In exploring how the financial abuse of potentially vulnerable people can be reframed so that it is hidden by process and procedure, this paper offers an insight into the means by which it is possible to promote transparency and greater accountability.